Bonding between oxide ceramics and adhesive cement systems: A systematic review. Issue 2 (9th October 2013) - Papia, Evaggelia; Larsson, Christel; du Toit, Madeleine; von Steyern, Per Vult
Abstract The following aims were set for this systematic literature review: (a) to make an inventory of existing methods to achieve bondable surfaces on oxide ceramics and (b) to evaluate which methods might provide sufficient bond strength. Current literature of in vitro studies regarding bond strength achieved using different surface treatments on oxide ceramics in combination with adhesive cement systems was selected from PubMed and systematically analyzed and completed with reference tracking. The total number of publications included for aim a was 127 studies, 23 of which were used for aim b. The surface treatments are divided into seven main groups: as‐produced, grinding/polishing, airborne particle abrasion, surface coating, laser treatment, acid treatment, and primer treatment. There are large variations, making comparison of the studies difficult. An as‐produced surface of oxide ceramic needs to be surface treated to achieve durable bond strength. Abrasive surface treatment and/or silica‐coating treatment with the use of primer treatment can provide sufficient bond strength for bonding oxide ceramics. This conclusion, however, needs to be confirmed by clinical studies. There is no universal surface treatment. Consideration should be given to the specific materials to be cemented and to the adhesive cement system to be used. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 395–413, 2014.